2012
DOI: 10.1371/journal.pgen.1002524
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tgif Function Causes Holoprosencephaly by Disrupting the Shh Signaling Pathway

Abstract: Holoprosencephaly (HPE) is a severe human genetic disease affecting craniofacial development, with an incidence of up to 1/250 human conceptions and 1.3 per 10,000 live births. Mutations in the Sonic Hedgehog (SHH) gene result in HPE in humans and mice, and the Shh pathway is targeted by other mutations that cause HPE. However, at least 12 loci are associated with HPE in humans, suggesting that defects in other pathways contribute to this disease. Although the TGIF1 (TG-interacting factor) gene maps to the HPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 78 publications
(116 reference statements)
4
89
0
Order By: Relevance
“…It has previously been hypothesized that the closely related homeobox gene Tgif2 might compensate for the reduced activity of Tgif1 in certain tissues or developmental contexts, since it shares many of the functional attributes of Tgif1 (12). In addition, Tgif1 and Tgif2 clearly perform overlapping functions during early embryonic development in mice (12,13). Furthermore, our data also show that SLAM cells from Tgif1 Ϫ/Ϫ mice express significantly higher levels of Tgif2 than SLAM cells from wild-type mice (see Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It has previously been hypothesized that the closely related homeobox gene Tgif2 might compensate for the reduced activity of Tgif1 in certain tissues or developmental contexts, since it shares many of the functional attributes of Tgif1 (12). In addition, Tgif1 and Tgif2 clearly perform overlapping functions during early embryonic development in mice (12,13). Furthermore, our data also show that SLAM cells from Tgif1 Ϫ/Ϫ mice express significantly higher levels of Tgif2 than SLAM cells from wild-type mice (see Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The majority of these mutations would cause a loss of protein function and are hypothesized to alter signaling by TGF-␤-related ligands (9)(10)(11). In mice, loss of both Tgif1 and Tgif2 is lethal, but epiblast-specific deletion of Tgif1 in combination with a null mutation in Tgif2 results in HPE, which is at least partly due to deregulation of Nodal signaling, suggesting that human TGIF1 mutations may cause HPE by affecting TGF-␤ signaling (12,13).…”
mentioning
confidence: 99%
“…This is achieved through the expression of specific signaling molecules in the dorsal forebrain, such as FGFs, BMPs and Wnts (Furuta et al, 1997;Grove et al, 1998;Crossley et al, 2001). In addition, transcription factors such as Six3, Tgif, Gli3 and Zic2, which are expressed by the RP, have also been implicated as regulators of dorsal forebrain development (Theil et al, 1999;Wallis et al, 1999;Warr et al, 2008;Taniguchi et al, 2012). Perturbation in the activity of these signaling molecules and transcription factors adversely affect the development of the dorso-medial forebrain-derived structures and may also lead to HPE.…”
Section: Introductionmentioning
confidence: 99%
“…275 OM mouse models have provided evidence of defects in the regulation of TGFβ signaling in the middle ear 71,73 , and prior studies have identified a link between HH signaling and the TGFβ pathway in holoprocencephaly and cancer. 263,264 Because of the connections between TGFβ signaling pathway and OM 71,73,95,96 and TGFβ and HH signaling pathways 263,264 , we investigated whether TGFβ regulated KIF7 expression. We also measured expression of other HH signaling pathway members, both upstream (PTCH1 and SUFU) and downstream (GLI1) of KIF7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…KIF7 lies within the Sonic hedgehog (SHH) pathway, which has been shown to interact with the TGFβ pathway. 263,264 Because of these connections, we sought to investigate whether the TGFβ pathway could regulate KIF7.…”
Section: Evaluation Of Tgfβ Signaling Pathway Regulation Of Kif7mentioning
confidence: 99%